(untitled) (Revista ABRA, 2011)
The democratic conception is analyzed, first from a theoretical-epistemological point of view, then in reference to the political consequences on social integration processes within modernity, and finally in relation to its possibilities in the creation of a new society focused on equality, diversity and welfare.